SAMARKAND JADIDS AND THEIR ROLE IN THE DEVELOPMENT OF SPIRITUAL VALUES THROUGH EDUCATION - Hamrayev Ergash (Bright Mind Publishing, 2025)
This article provides an in-depth analysis of the Jadid movement that emerged in the Turkestan region in the early 20th century, focusing specifically on its representatives in Samarkand and their distinctive contributions. Particular attention is given to the educational reforms initiated by the Samarkand Jadids, including their efforts to establish modern-method schools and their significant role in authoring textbooks and educational materials. The paper emphasizes that the central objective of the Jadids was to rescue the population from ignorance and illiteracy and to foster a spiritual awakening by strengthening national consciousness and identity. Moreover, the article highlights the Samarkand Jadids' approach to integrating education with national values, underscoring their pedagogical commitment to instilling high moral standards—such as patriotism, honesty, diligence, and justice—among the younger generation. Through education, they sought to achieve moral renewal within society and consistently worked to harmonize progressive ideas of their time with enduring national traditions.
Keywords: Samarkand Jadids, Jadid movement, educational reforms, new method schools, spiritual values, national revival, self-awareness, youth education, enlightenment, historical heritage.